Interconnected roles of mitochondrial carrier proteins ANT, PiT, and UCPs in proton transport - Tabefam, Marzieh; Swanson, Heidi K.; Smith, Matthew D.; Jelokhani-Niaraki, Masoud (Frontiers in Molecular Biosciences, 2025)
IntroductionAdenine nucleotide translocase (ANT), phosphate translocase (PiT), and uncoupling proteins (UCPs), all integral to oxidative phosphorylation, are among the carrier proteins of the mitochondrial inner membrane (MIM). While traditionally thought to function as monomers, their close proximity within the densely packed MIM suggests potential mutual interactions and formation of homo- and/or hetero-oligomers, the physiological implications of which are yet to be understood.MethodsWe investigated the conformations and proton transport activity of ANT1, PiT, UCP2 and UCP4 individually and in combination, to explore the possibility of hetero-oligomerization and functionally relevant interactions among the proteins. Monomeric proteins were reconstituted, individually and/or in combination, into model lipid membranes and the conformation, oligomeric state, and proton transport activities were assessed using biophysical approaches.ResultsUCP2 and UCP4 spontaneously assembled into functional tetramers, whereas ANT1 and PiT predominantly remained monomeric. The presence of cardiolipin in lipid membranes affected ANT1 oligomerization but had no influence on UCPs or PiT, suggesting that homotetramerization may be a characteristic of only a subset of mitochondrial carriers. Nevertheless, binary and ternary combinations of the proteins formed heterotetramers capable of proton transport. The UCP2-ANT1 combination showed significant proton transport, whereas proton transport by the UCP4-PiT combination was substantially lower, highlighting the specificity of interactions. Proton transport was differentially activated by free fatty acids; oleic acid was a better activator than palmitic acid. Inhibitory effects of purine nucleotides also varied across different protein combinations.DiscussionCollectively, our findings emphasize how interactions among these four mitochondrial carrier proteins may affect proton transport across the MIM and influence mitochondrial bioenergetics.